Studi Aplikatif tentang Kerendahan Hati dan Keteladanan Hamba Kristus pada Anggota Komsel Pradana, di GBI Stairway From Heaven, Bandung. Sebuah Refleksi atas Matius 11:29 - andri budiman (Sekolah Tinggi Teologia Kerusso Indonesia, 2021)
AbstractWith humility and example, servants of Christ will further build faith, provide a positive impactthrough exemplary repentance, spiritually and morally, and provide growth in faith accompanied byexample for cell group members. Applying humility and the example of a servant of Christ canpositively impact the cell group members where they are, both in society, the church, and theenvironment. That is why humility and the example of a servant of Christ are absolute things forevery true believer, and this is a critical topic to discuss and apply. The research method used is adescriptive qualitative research method. From the research results, it was found that the applicationof humility and the example of servants of Christ is nothing new. Since the Old Testament, humilityand being an example of a servant of God have been emphasized. In the New Testament, the LordJesus Christ, the Son of God and who became the Son of Man, always gives teaching, testimony, andcalls and shows learning to His disciples with humility and a dignified example. In general, humilityand the example of Christ can have a positive and more substantial impact than words alone. Theauthority and power of a servant of Christ, with humility and example, are very relevant to themembers of the cell group they teach or lead.